Unusual Clinical Presentation of Condyloma Acuminata in Elderly: A Case Report - Yufanti Sujudi; Dewi Lestarini; Devi Arofah Mumtazah; Mahda Rizki Liana; Meiuta Hening Prastiwi; Erlina (Asian Journal of Health Research, 2026)
Introduction: Condyloma acuminata is an anogenital wart caused by human papillomavirus (HPV), typically affecting sexually active individuals. However, atypical presentations in elderly patients without a history of sexual exposure are rare and may mimic malignant lesions, posing a diagnostic challenge. Case Presentation: A 72-year-old male patient presented to the dermatology and venerology outpatient clinic of Fatmawati Hospital with complaints of reddish spots on the penis accompanied by itching that had worsened over the past 2 weeks. The symptoms had been recurring intermittently for the past four years. The patient denied any risky sexual activity. On the dermatological examination at the initial visit, multiple, erythematous, verrucous, and nummular plaques were observed on the glans penis and sulcus. Acetowhite examination yielded positive results, and the histopathological examination suggested condyloma acuminata. The patient was treated with 25% podophyllin, 90% TCA, and glycyrrhizinic acid. Conclusion: This case underscores the importance of histopathological confirmation in elderly patients with atypical genital lesions mimicking malignancy. Careful diagnostic evaluation is essential to avoid overtreatment and misdiagnosis.